REAL ESTATE MARKET RESEARCH AT THE INTERNATIONAL LEVEL - Abishova A.U.; Mergenbaeva A.T.; Urazbayeva G.Zh. (Scientific Journal of Pedagogy and Economics, 2019)
The importance of the Kazakhstan real estate market as sectors of economy is confirmed by its high share in gross national product, high level of the income arriving in the budget from primary sale, leasing of the state and municipal real estate (including lands), receipt of charges in the budget of taxes from the real estate and transactions with it. Economic recovery of Kazakhstan, and alsoaspiration of the most part of the population to improvement of the housing conditions caused relevance of housing construction in the republic. Real estate objects, it is more, than other goods, are subject to the state impact that increases risk of loss of investments in these objects. The real estate - expensive goods, and for its acquisition the difficult financial schemes including pledge or offset of cost of a former real estate object (different types of mortgages), etc. are often used. Special characteristics of real estate objects as goods along with its special place in market economy cause need of rather wide range of social and economic information for positioning of these goods in the market. The real estate market is intended for rendering certain services and in the social and economic nature is close to the market of services. However it is impossible to claim that the real estate market is a component of the single market of services. Having a number of differences from financial assets, the real estate can be considered as a part of a total investment portfolio, allowing to reduce general risk and as an independent asset. Thus, purchase and sale of real estate objects is a movement of cost, revenue-producing. At the same time the real estate can be purchased as in production, and for personal reasons.